Optimization and control of one dimensional packed bed model of underground coal gasification. (November 2015) - Uppal, Ali Arshad; Bhatti, Aamer Iqbal; Aamir, Erum; Samar, Raza; Khan, Shahid Ahmed
Abstract : Highlights: Optimization and control of the UCG process is presented in this manuscript. The uncertainty in some model parameters is addressed by nonlinear optimization. SQP algorithm is used to solve the constrained nonlinear optimization problem. The results of solved model are compared with actual field trials. The Super twisting sliding mode controller is designed for the UCG process. The robustness of the algorithm is shown against the matched disturbance. Abstract: This paper discusses the optimization and control of the one dimensional (1-D) packed bed model of underground coal gasification (UCG) process for an actual UCG site. The optimization is performed to compensate for the uncertainty in coal and char ultimate analysis (caused by repeated measurements of different samples) and in steam to oxygen (O2 ) ratio at the reaction front. The constrained nonlinear optimization problem is solved by using state of the art sequential quadratic programing (SQP) algorithm to minimize the error between experimental and simulated heating values. The results of the optimized model are validated with actual filed trials which show a good match for heating value of the product gases. The super twisting controller, a second order sliding mode control (SOSMC) algorithm is successfully implemented on the process model, which keeps the heating value of the product gas at the desired level in the presence of the matched disturbance: steam produced from water influx from surrounding aquifers and due to the moisture content of the coal.